LLATO ferroelectric phase nbto solid-state electrolyte material and preparation method and application thereof

By doping Ag into LLTO and coating it with the NBTO ferroelectric phase, an LLATO@ferroelectric NBTO solid electrolyte was prepared, which solved the problems of leakage and interface instability in lithium-ion batteries, achieved high ionic conductivity and interface stability, and improved the cycle stability and performance of the battery under high current density.

CN122291664APending Publication Date: 2026-06-26HEFEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610550952.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-24
Publication Date
2026-06-26

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have risks of leakage and oxidation combustion due to their liquid electrolytes, and LLTO solid electrolytes have problems with high grain boundary impedance and interface instability, resulting in poor cycle stability of the battery at high current densities.

Method used

LLATO material was prepared by doping LLTO with Ag ions at the A site, and then LLATO was coated with NBTO ferroelectric phase to form LLATO@ferroelectric phase NBTO solid electrolyte. Uniform doping of Ag element and NBTO coating were achieved by sol-gel method, which enhanced the interface stability and conductivity.

Benefits of technology

It significantly improves the room temperature ionic conductivity and interface stability of lithium-ion batteries, suppresses lithium dendrite growth, and enhances the cycle stability and rate performance of the batteries, especially exhibiting excellent long cycle performance at high current densities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122291664A_ABST
    Figure CN122291664A_ABST
Patent Text Reader

Abstract

This invention provides an LLATO@ferroelectric phase NBTO solid electrolyte material, its preparation method, and its application, belonging to the field of lithium-ion solid electrolyte technology. This invention employs a sol-gel method for mixing and calcination to synthesize NBTO ferroelectric phase-coated LLATO lithium-ion conductors (Li). 0.33 La 0.457 Ag 0.1 TiO3@ x wt% Na 0.5 Bi 0.5 TiO3 (0< x ≤6). The LLATO@ferroelectric phase NBTO solid electrolyte material of the present invention exhibits excellent comprehensive performance, with a room temperature ionic conductivity of σ=1.08×10⁻⁶. ‑3 S / cm, relative to the room temperature ionic conductivity of the uncoated LLATO solid electrolyte (1.54 × 10⁻⁶). ‑4 The voltage (S / cm) is improved by an order of magnitude. In lithium symmetric battery tests, it maintains stable cycling after 2000 charge-discharge cycles at 0.1 mA and maintains stable voltage output at 1 mA.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion solid electrolyte technology, specifically relating to an LLATO@ferroelectric phase NBTO solid electrolyte conductor material and its preparation method, and its application in lithium-ion batteries. Background Technology

[0002] Electricity is one of the most widely used energy sources by humankind. Currently, the intermittency and instability of renewable energy power generation, such as wind and solar power, cause significant impacts on the power grid when these new energy power plants are connected to the grid on a large scale. Energy storage systems play a crucial role in balancing, regulating, and peak shaving / valley filling. Electrochemical energy storage technology is one of the energy storage technologies with promising prospects for industrial application.

[0003] Among various commercially available rechargeable chemical energy storage devices, lithium-ion batteries possess advantages such as high power density, low self-discharge rate, no memory effect, long cycle life, and low environmental pollution, making them widely used in portable electronic products. In recent years, the application of lithium-ion batteries in electric vehicles has attracted significant attention. Currently, most commercially available lithium-ion batteries use liquid electrolytes. Although liquid electrolytes have good ionic conductivity, they present safety issues in practical applications, such as leakage and oxidation combustion. These safety concerns limit the application of lithium-ion batteries in electric vehicles and large-scale renewable energy (such as solar and wind) storage.

[0004] Replacing the liquid electrolyte in traditional lithium-ion batteries with a solid electrolyte can significantly improve the safety and extend the lifespan of lithium-ion batteries, and further increase their power density. Therefore, high-performance lithium-ion solid electrolytes have become a research hotspot in recent years.

[0005] Li 3x La 2 / 3-x TiO3 (LLTO), as a perovskite-type solid electrolyte, possesses excellent thermal stability and safety. Furthermore, its extremely low electronic conductivity and wide electrochemical window (exceeding 8V) have attracted considerable research interest. However, LLTO faces the following challenges: although LLTO exhibits very high bulk ionic conductivity (reaching 1.0 × 10⁻⁶), it still presents several limitations. -3 However, it exhibits significant grain boundary resistance, resulting in a low total ionic conductivity (only 1.0 × 10⁻⁶ S / cm). -5 S / cm); as well as poor interface wettability and uneven distribution of space charge layer, resulting in uneven current distribution, which leads to lithium dendrite growth under long-term cycling under high current density conditions, ultimately causing battery failure.

[0006] To address the two main problems mentioned above, this invention provides an LLATO@ferroelectric phase NBTO solid electrolyte material and applies it to lithium-ion batteries. Summary of the Invention

[0007] In order to overcome the shortcomings and deficiencies of the prior art, the primary objective of this invention is to provide an LLATO@ferroelectric phase NBTO solid electrolyte material. The solid electrolyte is prepared by doping LLTO with Ag ions at the A site to obtain LLATO, and then coating LLATO with NBTO ferroelectric phase. This electrolyte material has high ionic conductivity, high interfacial stability and good electrochemical performance.

[0008] The objective of this invention is achieved through the following solution: A solid electrolyte material of LLATO@ferroelectric phase NBTO, the chemical formula of which is Li 0.33 La 0.457 Ag 0.1 TiO3@ x wt% Na 0.5 Bi 0.5 TiO3, 0< x ≤6, of which the content of Ag element is determined to be 0.1 mol. x The percentage of NBTO (ferroelectric phase) added.

[0009] In a preferred embodiment of the present invention, the LLATO@ferroelectric phase NBTO solid electrolyte material exhibits excellent overall performance, with a room temperature ionic conductivity of σ = 1.08 × 10⁻⁶. -3 S / cm, relative to the room temperature ionic conductivity of the uncoated LLATO solid electrolyte (1.54 × 10⁻⁶). -4 The S / cm ratio is increased by an order of magnitude, and it exhibits excellent cycle stability and rate performance at large limiting current densities and low limiting current densities. It effectively alleviates the lithium dendrite growth problem and significantly improves the interface stability between the electrolyte and the lithium metal anode. In lithium symmetric battery tests, it maintains stable cycling after 2000 charge-discharge cycles at 0.1mA and maintains stable voltage output at 1mA.

[0010] Another objective of this invention is to provide a method for preparing the above-mentioned LLATO@ferroelectric phase NBTO solid electrolyte material, the specific preparation steps of which are as follows: (1) Weigh out the lithium source, lanthanum source, titanium source and silver source according to the composition of the solid electrolyte, and weigh out triethanolamine; (2) Mix the titanium source and triethanolamine and dissolve them in ethanol to form solution A. (3) Dissolve the lithium source, lanthanum source and silver source in deionized water to form solution B; (4) Add solution B to solution A and stir until homogeneous, and continue heating and stirring until sol C is formed; (5) The sol C was dried to obtain a dry gel, which was then calcined at high temperature to obtain perovskite precursor powder D; (6) Weigh out the sodium source, bismuth source and titanium source according to the ferroelectric phase composition, and weigh out triethanolamine; (7) Mix the titanium source and triethanolamine and dissolve them in ethanol to form solution E; (8) Add the precursor powder D, sodium source and bismuth source to solution E in sequence, and keep the solution heated and stirred in a water bath until a sol F is formed; (9) The sol F was dried to obtain a dry gel, which was then calcined at high temperature to obtain perovskite precursor powder G; (10) Polyvinyl alcohol was added to the precursor powder G for granulation, and then pressed into tablets, debinding and high-temperature sintering were performed in sequence to obtain the LLATO@ferroelectric phase NBTO solid electrolyte material.

[0011] As a preferred embodiment of the present invention, in steps (1) and (6), the lithium source is selected from at least one of lithium nitrate, lithium carbonate, lithium acetate, lithium chloride, and lithium oxalate; the lanthanum source is selected from at least one of lanthanum nitrate, lanthanum chloride, lanthanum acetate, and lanthanum carbonate; the titanium source is at least one of tetrabutyl titanate, ethyl titanate, and isopropyl titanate; the silver source is at least one of silver nitrate, silver carbonate, and silver methanesulfonate; the sodium source is at least one of sodium nitrate, sodium carbonate, sodium chloride, and sodium acetate; and the bismuth source is at least one of bismuth nitrate, bismuth carbonate, and bismuth chloride.

[0012] As a preferred embodiment of the present invention, in step (1), the molar ratio of the amount of titanium source to triethanolamine weighed is (2~4):1.

[0013] As a preferred embodiment of the present invention, in step (1), the amount of lithium source weighed is 1.0 to 1.2 times the theoretical amount of lithium source determined according to the composition of the solid electrolyte.

[0014] As a preferred embodiment of the present invention, in step (2), the volume of the solvent ethanol is 90~110 ml.

[0015] As a preferred embodiment of the present invention, in step (3), the volume of the solvent deionized water is 90~110 ml.

[0016] As a preferred embodiment of the present invention, in step (4), the process of adding solution B to solution A is direct mixing; The addition of solution B was always accompanied by water bath heating, with a heating temperature of 40~80 ℃; After solution B is added dropwise, maintain a water bath with stirring. The heating temperature is 40~80 ℃, and the stirring time is 16~32 h.

[0017] As a preferred embodiment of the present invention, in step (5), the drying temperature is 60~100 ℃ and the drying time is 3~6 h; The high-temperature calcination temperature is 800~1000 ℃, and the drying time is 4~8 h.

[0018] As a preferred embodiment of the present invention, in step (6), the molar ratio of the amount of titanium source to triethanolamine weighed is (2~4):1.

[0019] As a preferred embodiment of the present invention, in step (7), the volume of the solvent ethanol is 90~110 ml.

[0020] As a preferred embodiment of the present invention, in step (8), the precursor powder D, sodium source and bismuth source are added to solution E in sequence, which is always accompanied by water bath heating, and the heating temperature is 40~80 ℃. After adding solution E, maintain water bath heating and stirring at a temperature of 40-80 °C for 16-32 h.

[0021] As a preferred embodiment of the present invention, in step (9), the drying temperature is 60~100 ℃ and the drying time is 3~6 h; The high-temperature calcination temperature is 800~1000 ℃, and the calcination time is 4~8 h.

[0022] As a preferred embodiment of the present invention, in step (10), the mass ratio of polyvinyl alcohol to precursor powder G is (0.04~0.06):1; The tableting pressure is 53~57 MPa, and the holding time is 1~5 min; The adhesive removal treatment temperature is 500~700 ℃, and the heat preservation time is 6~8 h; The high-temperature sintering process is as follows: the temperature is increased to 900 ℃ at a heating rate of 5 ℃ / min and held for 6 h, then decreased to 500 ℃ at a cooling rate of 5 ℃ / min, and then cooled to room temperature with the furnace.

[0023] Mechanism of this invention: This invention successfully introduces Ag ions into the perovskite lattice using the sol-gel method, and then coats the already prepared LLATO surface with ferroelectric NBTO, thereby preparing an LLATO@ferroelectric NBTO perovskite solid electrolyte material with significant performance advantages. This method fully utilizes the molecular-level mixing advantages of the sol-gel process, achieving uniform Ag doping and uniform NBTO coating, maintaining the perovskite structure while using Ag... + For La in the crystal lattice 3 + The substitution of Ag induces controllable lattice distortion and expansion, effectively increasing the bottleneck size of Li ions. + < La3+ After replacing the A-site ion with a higher valence state, maintaining charge neutrality will generate a higher concentration of vacancies, thus providing Li + Diffusion provides more free space to improve conductivity and facilitates TiO6 octahedral tilting behavior, lowering the activation energy and thus enhancing conductivity. Simultaneously, the introduction of the ferroelectric NBTO phase into the obtained LLATO allows for spontaneous polarization, promoting the establishment of an internal electric field and generating a new electric field between the metal electrode and the solid state, achieving a locally opposite and uniform distribution of space charge. This effectively suppresses lithium dendrites at high limiting current densities. This breakthrough in key technology successfully solves the long-standing problems of high grain boundary resistance and interfacial instability in LLTO electrolytes. This strategy of simultaneously improving bulk ionic conductivity and enhancing interfacial stability through doping and introducing a ferroelectric phase not only significantly improves the cycle stability of solid-state batteries but also provides new ideas and directions for the subsequent development of oxide solid-state electrolyte materials.

[0024] Compared with the prior art, the beneficial effects of the present invention are: (1) This invention employs Ag to precisely dope the La sites of LLTO materials, improving the symmetry and stability of the crystal structure and suppressing harmful phase transitions and lattice distortions. Because r Ag + =0.115 nm> r La 3+ =0.1032 nm, resulting in a larger lattice parameter and expanding the Li + The bottleneck size is smaller, and [TiO6] octahedral tilting behavior is more likely to occur, reducing the activation energy and thus improving conductivity, and Ag + < La 3+ Replacing the larger valence state La-site ion while maintaining charge neutrality will generate a higher concentration of vacancies, thus creating Li+. + Diffusion provides more free space, resulting in a significant increase in conductivity.

[0025] (2) Introducing ferroelectric phase NBTO to coat LLATO is beneficial for spontaneous polarization to establish an internal electric field, generating a new electric field between the metal electrode and the solid, achieving a uniform distribution of local opposite space charge, and effectively suppressing lithium dendrites under high limiting current density.

[0026] (3) The introduction of ferroelectric phase during crack propagation can bridge and deflect cracks, and can also consume the driving force of crack propagation, thus improving fracture toughness.

[0027] (4) A field-responsive grain boundary was designed to prevent Li from nucleating through a weakened local electric field. The ferroelectric phase is distributed on the grain boundary. Attached Figure Description

[0028] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0029] Figure 1 XRD and (200) characteristic peak spectra of the solid electrolytes prepared in Examples 1, 2, 3 and 4.

[0030] Figure 2 This is a microstructure diagram of the solid electrolyte material prepared in Example 1.

[0031] Figure 3 This is a microstructure diagram of the solid electrolyte material prepared in Example 3.

[0032] Figure 4 The PFM amplitude represents the impedance performance of the solid electrolyte materials prepared in Example 1 and Example 3.

[0033] Figure 5 The impedance performance diagram of the solid electrolyte material prepared in Example 1 in the range of 30-140℃ is shown.

[0034] Figure 6 The lithium symmetric cycling spectrum of the solid electrolyte material prepared in Example 3. Detailed Implementation

[0035] The following will provide a clear and complete description of the technical solutions involved in the embodiments. It should be clearly noted that the embodiments detailed herein are merely a part of the numerous embodiments of the present invention, and not all of them. For those skilled in the art, all other embodiments derived from the embodiments provided in this invention without creative effort are within the protection scope of this invention. Unless otherwise specified, the materials involved in the following embodiments are commercially available. Unless otherwise specified, the methods described are conventional methods. The amounts of each component are expressed in parts by mass and parts by volume, in g and mL.

[0036] Example 1 This embodiment 1 provides a chemical formula Li 0.33 La 0.457 Ag 0.1 TiO3@1wt% Na 0.5 Bi 0.5 The specific preparation steps of the TiO3 Ag-doped ferroelectric phase NBTO-coated perovskite oxide solid electrolyte are as follows: (1) Weigh out 2.501g lithium nitrate, 19.777g lanthanum nitrate, 33.999g tetrabutyl titanate and 1.698g silver nitrate according to the solid electrolyte composition. The molar ratio of tetrabutyl titanate to triethanolamine is 3.5:1. Weigh out 4.262g triethanolamine. Control the total amount of lithium element fed to exceed the stoichiometric theoretical value by 10 wt.%. (2) Tetrabutyl titanate and triethanolamine are mixed and dissolved in 100 ml of ethanol to form solution A. (3) Dissolve lithium nitrate, lanthanum nitrate and silver nitrate in 100 ml of deionized water to form solution B; (4) Add solution B to solution A and stir until homogeneous. Then, stir the resulting mixture at 60 °C for 24 h to allow the substances in the solution to react fully until a stable sol C is formed. (5) Transfer the sol C to the drying oven and then put the gel into the drying oven and dry it at 80°C for 6 hours to obtain the dry gel. Place the dry gel in a muffle furnace and calcine it at 900°C for 6 hours to obtain the perovskite precursor powder D. (6) Weigh out 0.034 g of sodium nitrate, 0.108 g of bismuth nitrate and 0.272 g of tetrabutyl titanate according to the ferroelectric phase composition. The molar ratio of tetrabutyl titanate to triethanolamine is 3.5:1. Weigh out 0.034 g of triethanolamine. (7) Tetrabutyl titanate and triethanolamine are mixed and dissolved in 100 ml of ethanol to form solution E; (8) Add the precursor powder D, sodium nitrate and bismuth nitrate to solution E in sequence, and stir the resulting mixture at 60 °C for 24 h to allow the substances in the solution to react fully until a stable sol F is formed; (9) Transfer the sol F to the drying oven and then put the gel into the drying oven and dry it at 80 °C for 6 h to obtain the dry gel. Place the dry gel in a muffle furnace and calcine it at 900 °C for 6 h to obtain the perovskite precursor powder G. (10) 5 wt.% polyvinyl alcohol was added to the precursor powder G for granulation, and a uniform pressure of 55 MPa was applied to dry press to prepare a Φ12 mm × 1 mm circular blank. The pressed blank was kept at 600 °C for 7 h in a muffle furnace to remove the binder. The blank after binder removal was heated to 1100 °C at a heating rate of 5 °C / min and kept at 6 h. Then it was cooled to 500 °C at a cooling rate of 5 °C / min and finally cooled to room temperature with the furnace to obtain a solid electrolyte sheet of LLATO@ferroelectric phase NBTO.

[0037] Example 2 The difference between Example 2 and Example 1 is that x=2, and the chemical formula of the electrolyte material is Li. 0.33 La0.457 Ag 0.1 TiO3@2wt% Na 0.5 Bi 0.5 TiO3.

[0038] In step (6), according to the ferroelectric phase composition, 0.068g of sodium nitrate, 0.216g of bismuth nitrate and 0.544g of tetrabutyl titanate are weighed. The molar ratio of tetrabutyl titanate to triethanolamine is 3.5:1. 0.068g of triethanolamine is weighed.

[0039] The preparation process is the same as in Example 1.

[0040] Example 3 The difference between Example 3 and Example 1 is that x=4, and the chemical formula of the electrolyte material is Li. 0.33 La 0.457 Ag 0.1 TiO3@4wt% Na 0.5 Bi 0.5 TiO3.

[0041] In step (6), according to the ferroelectric phase composition, 0.136g of sodium nitrate, 0.432g of bismuth nitrate and 1.088g of tetrabutyl titanate are weighed. The molar ratio of tetrabutyl titanate to triethanolamine is 3.5:1. 0.136g of triethanolamine is weighed.

[0042] The preparation process is the same as in Example 1.

[0043] Example 4 The difference between Example 4 and Example 1 is that x=6, and the chemical formula of the electrolyte material is Li. 0.33 La 0.457 Ag 0.1 TiO3@6wt% Na 0.5 Bi 0.5 TiO3.

[0044] In step (6), according to the ferroelectric phase composition, 0.204g of sodium nitrate, 0.648g of bismuth nitrate and 1.632g of tetrabutyl titanate are weighed. The molar ratio of tetrabutyl titanate to triethanolamine is 3.5:1. 0.204g of triethanolamine is weighed.

[0045] The preparation process is the same as in Example 1.

[0046] Comparative Example 1 Comparative Example 1 provides a chemical formula Li 0.33 La 0.557 The specific preparation steps of the TiO3 perovskite oxide solid electrolyte material are as follows: (1) Weigh out 2.501g lithium nitrate, 24.105g lanthanum nitrate and 33.999g tetrabutyl titanate according to the solid electrolyte composition. The molar ratio of tetrabutyl titanate to triethanolamine is 3.5:1. Weigh out 4.262g triethanolamine. Control the total amount of lithium element fed to exceed the stoichiometric theoretical value by 10 wt.%. (2) Tetrabutyl titanate and triethanolamine are mixed and dissolved in 100 ml of ethanol to form solution A. (3) Dissolve lithium nitrate, lanthanum nitrate and silver nitrate in 100 ml of deionized water to form solution B; (4) Add solution B to solution A and stir until homogeneous. Then, stir the resulting mixture at 60 °C for 24 h to allow the substances in the solution to react fully until a stable sol C is formed. (5) Transfer the sol C to the drying oven and then put the gel into the drying oven and dry it at 80°C for 6 hours to obtain the dry gel. Place the dry gel in a muffle furnace and calcine it at 900°C for 6 hours to obtain the perovskite precursor powder D. (6) Add 5 wt.% polyvinyl alcohol to the precursor powder D for granulation, and apply a uniform pressure of 55 MPa to dry press and form a Φ12 mm × 1 mm circular blank. Hold the pressed blank at 600 °C for 7 h in a muffle furnace to remove the binder. After removing the binder, heat the blank to 1100 °C at a heating rate of 5 °C / min and hold for 6 h. Then, cool it to 500 °C at a cooling rate of 5 °C / min and finally cool it to room temperature with the furnace to obtain the LLTO solid electrolyte sheet.

[0047] Comparative Example 2 Comparative Example 2 provides a chemical formula Li 0.33 La 0.457 Ag 0.1 The TiO3 perovskite oxide solid electrolyte material is the same as Comparative Example 1 in all other technical aspects. The only difference is that in step (1) of Comparative Example 2, 19.777 g of lanthanum nitrate and 1.698 g of silver nitrate are weighed.

[0048] Comparative Example 3 Comparative Example 3 provides a chemical formula Li 0.33 La 0.557 TiO3@1wt% Na 0.5 Bi 0.5 The perovskite oxide solid electrolyte material of TiO3 is the same as that in Example 3, except that in step (1) of Comparative Example 2, 24.105g of lanthanum nitrate is weighed and silver nitrate is not added.

[0049] Comparative Example 4 Comparative Example 4 provides a chemical formula Li0.33 La 0.457 Ag 0.2 The perovskite oxide solid electrolyte of TiO3 is the same as that of Comparative Example 1, except that in step (1) of Comparative Example 4, 15.450 g of lanthanum nitrate and 3.397 g of silver nitrate are weighed.

[0050] The total ionic conductivity and cycling performance of the electrolyte materials prepared in Examples 1-4 and Comparative Examples 1-4 were tested. The prepared materials were also subjected to X-ray diffraction, electron microscopy, and PFM testing. The test results are shown in Table 1. Figures 1-5 The results and testing methods are as follows: (1) Preparation of solid electrolyte sheet: The prepared solid electrolyte sheet is polished with sandpaper until the surface is reflective, and then gold spraying is performed on the surface. (2) Ionic conductivity test: The prepared solid electrolyte sheet was tested on an electrochemical workstation at a test temperature of 25℃ and a test frequency of 0.01 Hz-1 MHz. The impedance of the solid electrolyte sheet was obtained by EIS test and the value was calculated using the formula σ. Li + =L / RS The ionic conductivity is calculated as follows: R is the total impedance, L is the thickness of the solid electrolyte sheet, and S is the area of ​​the solid electrolyte sheet.

[0051] (3) Cyclic test: The prepared solid electrolyte sheet was assembled into a symmetrical battery and its performance at 0.1 mA / cm² was tested. -2 Long-cycle performance at current density.

[0052] Table 1. Total ionic conductivity and cycle performance test results of electrolyte materials in Examples 1-4 and Comparative Examples 1-4

[0053] As shown in Table 1, the solid electrolyte material of the present invention exhibits significantly improved total ionic conductivity and cycle stability. Further comparative analysis is provided below: (1) Examples 1-4 were implemented on samples with different contents of NBTO ferroelectric phase. By comparing the ionic conductivity, it can be found that under the premise of controlling the Ag doping concentration to be consistent, the spontaneous polarization field of NBTO ferroelectric phase can regulate the lithium ion concentration distribution near the LLTO interface. By forming a high-concentration lithium ion accumulation layer, ion transport is promoted, that is, the total ionic conductivity is increased. However, since the ionic conductivity of NBTO ferroelectric phase itself is low, excessive coating will lead to the formation of high-resistivity material, resulting in a decrease in total ionic conductivity. By the battery stable operation time, it was found that the stable operation time performance of Examples 1-4 is excellent. This is because the spontaneous polarization of NBTO ferroelectric phase establishes the establishment of an internal electric field, generating a new electric field between the metal electrode and the solid, realizing the local opposite uniform distribution of space charge, effectively suppressing lithium dendrites, and making the battery operate stably.

[0054] (2) By comparing Comparative Examples 1, 2, and 4, it can be seen that doping with Ag alone can improve the performance of LLTO solid electrolyte to a certain extent. This is because Ag, after replacing the A-site ions with larger valence states, remains charge neutral, generating a higher concentration of vacancies for Li. + Diffusion provides more free space, leading to improved performance; however, if the Ag doping level is too high, it can actually hinder performance. + Occupy Li + The empty space that moves obstructs Li + Transport can reduce the ionic conductivity and cycle stability of solid electrolytes. Therefore, this invention selects a fixed Ag content of 0.1 as the most suitable ratio.

[0055] (3) A comparison of Example 3, Comparative Example 1, and Comparative Example 3 shows that when only 4 wt% NBTO is coated, the ionic conductivity and cycle stability of LLTO are slightly improved, but not significantly. For the solid electrolyte in the examples that is doped with an appropriate amount of Ag and coated with ferroelectric NBTO, its ionic conductivity and cycle stability are significantly improved, indicating that the LLATO@ferroelectric NBTO solid electrolyte of the present invention has superior performance.

[0056] Figure 1 The LLATO@ferroelectric phases in Examples 1, 2, 3, and 4 are shown. x wt% NBTO ( x XRD patterns and (200) characteristic peak patterns of the solid electrolyte system (components 1, 2, 4, and 6) were obtained. The diffraction peaks of all components corresponded completely to the LLATO standard card, and no impurity phases were observed. The presence of an NBTO phase was discovered by locally magnifying the (200) characteristic peak.

[0057] Figure 2 The image shows a SEM image of the solid electrolyte in the LLATO@ferroelectric phase 1wt% NBTO system in Example 1, proving that it formed a dense solid electrolyte.

[0058] Figure 3 The image shows a SEM image of the solid electrolyte in the LLATO@ferroelectric phase 4wt% NBTO system in Example 3, proving that it formed a dense solid electrolyte.

[0059] Figure 4 PFM tests were performed on the LLATO@ferroelectric phase xwt% NBTO solid electrolyte in Examples 1 and 3. The test results showed that ferroelectric effect was generated in both Examples 1 and 3 when a +10V voltage was applied, and the ferroelectric effect became more obvious with the increase of coating amount.

[0060] Figure 5 For Example 3, LLATO@ was used in the range of 30-140 °C. The impedance properties of 4wt% NBTO solid electrolyte material, in x In a sample with a concentration of 4 wt%, Li + It exhibits low grain boundary resistance and high conductivity. At T=25℃, the conductivity is σ=1.08×10⁻⁶. -3 S / cm, compared to 1.54 × 10⁻⁶ for Ag-doped only. -4 The S / cm increased by an order of magnitude, and for the same component, the conductivity showed a positive correlation with temperature as the temperature increased.

[0061] Figure 6 The Li-symmetric cell assembled based on Example 3 was demonstrated at 0.1 mA / cm². -2 The battery exhibits excellent interface stability and cycle durability, with long-term cycle performance at current density and stable operation for over 2500 hours.

[0062] The content described above represents only a preferred embodiment of the present invention. However, the implementation of the present invention is not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention should be considered equivalent substitutions and are included within the protection scope of the present invention.

Claims

1. An LLATO@ferroelectric phase NBTO solid electrolyte material, characterized in that, The chemical formula of the electrolyte material is Li. 0.33 La 0.457 Ag 0.1 TiO3@ x wt% Na 0.5 Bi 0.5 TiO3, where 0 < x ≤6, the Ag element content is determined to be 0.

1. x Depending on the mass percentage of ferroelectric NBTO added, different mass fractions of NBTO were used to coat the surface of LLATO solid electrolyte. This reduced the activation energy while maintaining the perovskite structure, thereby improving conductivity, effectively suppressing lithium dendrites, and improving interface stability.

2. The preparation method of the LLATO@ferroelectric phase NBTO solid electrolyte material as described in claim 1, characterized in that, The preparation steps are as follows: (1) Weigh out the lithium source, lanthanum source, titanium source and silver source according to the composition of the solid electrolyte, and weigh out triethanolamine; (2) Mix the titanium source and triethanolamine and dissolve them in ethanol to form solution A. (3) Dissolve the lithium source, lanthanum source and silver source in deionized water to form solution B; (4) Add solution B to solution A and stir until homogeneous, and continue heating and stirring until sol C is formed; (5) The sol C was dried to obtain a dry gel, which was then calcined at high temperature to obtain perovskite precursor powder D; (6) Weigh out the sodium source, bismuth source and titanium source according to the composition of the ferroelectric phase, and weigh out triethanolamine; (7) Mix the titanium source and triethanolamine and dissolve them in ethanol to form solution E; (8) Add the precursor powder D, sodium source and bismuth source to solution E in sequence, and keep the solution heated and stirred in a water bath until a sol F is formed; (9) The sol F was dried to obtain a dry gel, which was then calcined at high temperature to obtain perovskite precursor powder G; (10) Polyvinyl alcohol was added to the precursor powder G for granulation, and then pressed into tablets, debinding and high-temperature sintering were performed in sequence to obtain the LLATO@ferroelectric phase NBTO solid electrolyte.

3. The preparation method according to claim 2, characterized in that, In steps (1) and (6), the lithium source is selected from at least one of lithium nitrate, lithium carbonate, lithium acetate, lithium chloride, and lithium oxalate; the lanthanum source is selected from at least one of lanthanum nitrate, lanthanum chloride, lanthanum acetate, and lanthanum carbonate; the titanium source is at least one of tetrabutyl titanate, ethyl titanate, and isopropyl titanate; the silver source is at least one of silver nitrate, silver carbonate, and silver methanesulfonate; the sodium source is at least one of sodium nitrate, sodium carbonate, sodium chloride, and sodium acetate; and the bismuth source is at least one of bismuth nitrate, bismuth carbonate, and bismuth chloride.

4. The preparation method according to claim 2, characterized in that, In step (1), the molar ratio of titanium source to triethanolamine is (2~4):1, and the amount of lithium source weighed is 1.0~1.2 times the theoretical amount of lithium source determined according to the composition of solid electrolyte; in step (6), the molar ratio of titanium source to triethanolamine weighed is (2~4):

1.

5. The preparation method according to claim 2, characterized in that, In step (4), the process of adding solution B to solution A is direct mixing. The process of adding solution B is always accompanied by water bath heating, with a heating temperature of 40~80 ℃. After the solution B is added, the water bath is kept heated and stirred, with a heating temperature of 40~80 ℃ and a stirring time of 16~32 h.

6. The preparation method according to claim 2, characterized in that, In step (5), the drying temperature is 60~100℃ and the drying time is 3~6 h; the high-temperature calcination temperature is 800~1000℃ and the drying time is 4~8 h.

7. The preparation method according to claim 2, characterized in that, In step (8), the precursor powder D, sodium source and bismuth source are added to solution E in sequence, and water bath heating is always carried out. The heating temperature is 40~80 ℃. After the addition of solution E is completed, water bath heating and stirring are maintained. The heating temperature is 40~80 ℃ and the stirring time is 16~32 h.

8. The preparation method according to claim 2, characterized in that, In step (9), the drying temperature is 60~100℃ and the drying time is 3~6 h; the high-temperature calcination temperature is 800~1000 ℃ and the calcination time is 4~8 h.

9. The preparation method according to claim 2, characterized in that, In step (10), the mass ratio of polyvinyl alcohol to precursor powder G is (0.04~0.06):1; the tableting pressure is 53~57 MPa, and the holding time is 1~5 min; the debinding temperature is 500~700 ℃, and the holding time is 6~8 h; the high-temperature sintering process is as follows: the temperature is raised to 900 ℃ at a heating rate of 5 ℃ / min and held for 6 h, then the temperature is lowered to 500 ℃ at a cooling rate of 5 ℃ / min, and then cooled to room temperature with the furnace.

10. The application of the LLATO@ferroelectric phase NBTO solid electrolyte material as described in claim 1 in lithium-ion batteries, wherein the room temperature ionic conductivity is σ = 1.08 × 10⁻⁶. -3 S / cm, at 0.1 mAcm -2 At current density, the battery achieves stable operation for 2500 hours of long-term cycling.